Local recurrence of diminutive colorectal polyps after cold forceps polypectomy with jumbo forceps followed by magnified narrow-band imaging: a multicenter prospective study - Kuwai, Toshio; Yamada, Takuya; Toyokawa, Tatsuya; Iwase, Hiroaki; Kudo, Tomohiro; Esaka, Naoki; Ohta, Hajime; Yamashita, Haruhiro; Hosoda, Yasuo; Watanabe, Noriko; Harada, Naohiko (Endoscopy, 2019)
Background Cold polypectomy has been increasingly used to remove diminutive colorectal polyps. We evaluated the local recurrence rate of diminutive polyps at the 1-year follow-up after cold forceps polypectomy (CFP).Methods In a prospective, multicenter, observational cohort study, patients with diminutive colorectal polyps ( ≤ 5 mm) were treated by CFP using jumbo forceps followed by magnified narrow-band imaging (NBI). Patients were assessed for local recurrence at 1-year follow-up. Risk factors associated with local recurrence were analyzed using logistic regression analysis.Results Overall, 955 lesions were resected in 471 patients who completed the 1-year follow-up. The endoscopic complete resection rate was 99.4 %. Immediate and delayed bleeding occurred in 0.8 % and 0.2 % of cases, respectively, with no perforations observed. Local recurrence occurred in 2.1 % of cases at the 1-year follow-up. Univariable analyses indicated that polyps > 3 mm (P < 0.01) and immediate bleeding (P = 0.04) were significantly associated with local recurrence. A trend was observed for patients ≥ 65 years (P = 0.06) and fractional resection (P = 0.09). Multivariable analyses confirmed that lesions > 3 mm were significantly associated with local recurrence (odds ratio 3.4, P = 0.02).Conclusions CFP with jumbo forceps followed by NBI-magnified observation had a low local recurrence rate and is an acceptable therapeutic option for diminutive colorectal polyps. Although we recommend limiting the use of CFP with jumbo forceps to polyps ≤ 3 mm in size, future comparative studies are needed to make recommendations on cold polypectomy using either forceps or snares as the preferred approach for diminutive polyp resection.